China’s influence on Taiwan’s media and politics - Hsu, Chien-Jung (Przegląd Politologiczny, 2018)
Taiwan’s democracy and freedom of the press provide the Chinese authorities with an opportunity to use Taiwanese businessmen to influence Taiwan’s media outlets and politics. China uses three inter-related strategies to influence Taiwan’s media in this way: persuading businessmen with pro-China views to purchase Taiwanese media outlets, pressuring existing media owners, and placing advertisements in Taiwan’s media in order to purchase political influence. In addition, the Chinese government also employs cyber-propaganda strategy to attack Taiwanese political parties and politicians.